Saillance physique et saillance cognitive - Frédéric Landragin (Corela)
Salience phenomena put an element from a linguistic or visual message forward. By confronting works resulting from various research fields, we propose a classification of the factors that make an entity salient in a linguistic utterance or in a visual scene. Some of these factors depend only on the physical characteristics of the message. We then talk about physical salience (or P-salience). Other factors depend on the subject’s cognitive processes. We then talk about cognitive salience (or C-salience). Considering this classification, we show that P-salience and C-salience concepts do not rely on the modality (linguistic or visual) to which they apply. This allows us to lay the foundations for a generic characterization of physical salience, and to draw some conclusions concerning the information structure concept.